Developing Guided Discovery Based Biology Teaching Material Supported by Pictorial Analysis (Universitas Negeri Semarang, 2018)
Most of students still consider the subject of classification to be the most difficult subject. 33.989% of the students chose the classification of living things subject as the most difficult subject. This study aims to determine the validity and impact of using learning material based on guided discovery with pictorial analysis on students' learning outcomes on the classification of living things subject. in junior high school. The research method used quasi experimental design with pre-test-post-test non equivalent control group design. Research development was done through 10 stages. This study was conducted at SMPN 1 Jati Kudus. The sample in this study was the students of grade 7th of academic year 2017/2018. Sampling was done by purposive sampling. The research revealed that learning material based on guided discovery with pictorial analysis has validation value with an average of 3.52 with the very valid criteria, but still needed revision on learning material. The learning material that is developed, it has a positive impact on student achievement. There are significant differences between the control class and the experimental class of the t test results obtained by the value of t arithmetic (5.041) > t table (1.988) indicates that there is the impact of using learning material based on guided discovery with pictorial analysis to the students achievement in the classification of living creatures subject. Guided discovery based teaching materials with pictorial analysis make students more active in learning with student activity level in experimental class 80,25% higher than control class that is equal to 70,36%.